Anti-proliferating and apoptosis-inducing activity of chemical compound FTI-6D in association with p53 in human cancer cell lines. (5th January 2023) - Inoue, Takato; Matsuda, Kazuaki; Matsusaka, Keisuke; Nakajima, Masaya; Takeno, Yukari; Miyazaki, Toko; Shintaku, Takahiko; Yoda, Natsumi; Saito, Takahiko; Ikeda, Eriko; Mano, Yasunobu; Shinohara, Kenichi; et al.
Abstract: Compounds with 3, 4-fused tricyclic indole (FTI) frameworks are attractive scaffolds for drug discovery. We synthesized FTI-6D, a compound with this framework, which was cytotoxic in several human cancer cell lines. FTI-6D induced apoptosis via activation of the p53 downstream mitochondria-related apoptotic pathway, characterized by an increased ratio of pro-apoptotic Bcl-2 family members to anti-apoptotic members. This change was followed by caspase-9 and caspase-3 cleavage and activation in two cancer cell lines, RKO and AGS. The anti-proliferating effect of FTI-6D was remarkably detected in eight cancer cells with wild-type TP53 ( TP53 _wt), including RKO and AGS, but not in seven cancer cells with mutated TP53 ( TP53 _mut). Additionally, p53 protein levels increased after FTI-6D treatment in TP53 _wt cancer cells, and the cytotoxic effect of FTI-6D was decreased by TP53 knockdown. Accordingly, the expression of p53 downstream genes involved in apoptotic signaling pathways, such as BBC3 and TP53INP1, and those involved in cell growth inhibition, such as CDKN1A, was upregulated in TP53 _wt cancer cells. These results suggest that the anti-proliferative and apoptosis-inducing activities of FTI-6D rely on p53 and the corresponding signaling processes. This study demonstrated that FTI-6D shows anti-cancer activity against TP53 _wt cancer cells. FTI-6D may have potential as a prototype compound for a new drug to utilize a functional p53 pathway in TP53 _wt cancer cells. Graphical abstract: Image 1 Highlights: FTI-6D is a chemically synthesized compound with 3, 4-fused tricyclic indole framework. FTI-6D showed anti-proliferating and apoptosis-inducing effects in cancer cells with wild-type TP53. FTI-6D activated the p53 downstream mitochondria-related apoptotic pathway. FTI-6D activated p53 target genes involved in apoptotic pathway and cell growth inhibition.